Denominación de Origen Protegida (DOP) de la Cerámica del Carmen de Viboral: beneficios percibidos en temas de internacionalización, protección intelectual y, desarrollo económico (2022)
The Protected Designation of Origin (PDO) is a recognition given by an organization to certain products that have their own characteristics attributable to a place of origin or traditional production techniques, which generate interest in consumers, improve the possibilities of access to other markets, obtain intellectual property rights and even generate better income in the marketing process. This favors the development of associative processes and provides opportunities to bet on the economic development of a region. In Eastern Antioquia, there is only one product that holds this certification, which is ceramics from Carmen de Viboral. Where not all artisans are members of the association and therefore, do not use this designation in order to make their products more attractive in the international context. For this research, a descriptive study was carried out, which, from the qualitative point of view, sought to know the perception of the members of the pottery producers association on issues such as brand positioning, internationalization processes, intellectual protection and, the little interest in obtaining the Geographical Indication certification, which was done through a semi-structured interview. For the quantitative, a survey was designed for two audiences, the first for producers who are attached to the association and the other for those who are producers of the good and who are not in the association, to measure knowledge of the certification, advantages obtained, among others.